2013
DOI: 10.1128/aem.01702-13
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity in Permafrost and Tallgrass Prairie Soils under Experimental Warming Conditions

Abstract: Soil fungi play a major role in terrestrial ecosystem functioning through interactions with soil structure, plants, micro-and mesofauna, and nutrient cycling through predation, pathogenesis, mutualistic, and saprotrophic roles. The diversity of soil fungi was assessed by sequencing their 28S rRNA gene in Alaskan permafrost and Oklahoma tallgrass prairie soils at experimental sites where the effect of climate warming is under investigation. A total of 226,695 reads were classified into 1,063 genera, covering 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 77 publications
(98 reference statements)
4
39
2
Order By: Relevance
“…On the other hand, the lack of detectable effect of experimental warming on bacterial community composition agrees with results from previous studies of soil microbes in grasslands (Penton et al, 2013), and temperate upland soils (Kuffner et al, 2012). In a somewhat different context, Cruz-Martinez et al (2009) also found community resistance to precipitation manipulation—despite considerable treatment effects on overlying vegetation.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the lack of detectable effect of experimental warming on bacterial community composition agrees with results from previous studies of soil microbes in grasslands (Penton et al, 2013), and temperate upland soils (Kuffner et al, 2012). In a somewhat different context, Cruz-Martinez et al (2009) also found community resistance to precipitation manipulation—despite considerable treatment effects on overlying vegetation.…”
Section: Discussionsupporting
confidence: 91%
“…The grassland soil ecosystem in the BioCON experimental site in Minnesota was dominated by Ascomycota (81% at aCO 2 and 77% at eCO 2 ) and Basidiomycota (11% at aCO 2 and 14% at eCO 2 ). Compared to the reports by previous studies (31,(58)(59)(60)(61), fungal community composition in soil varied greatly across different types of soil ecosystems. Such variations in fungal community composition between different studies might be caused by different coverage of different primer sets or phylogenetic markers (such as ITS versus 28S) (62), but more likely caused by plant species, soil, and/or climate differences (58).…”
Section: Discussioncontrasting
confidence: 47%
“…Glomeromycota is the phylum that most arbuscular mycorrhizal fungi belong to and was previously reported to be dominant in grasslands (63) and widespread among different global ecosystems (64). Since a previous study using the same primer set identified at least 15% Glomeromycota in an Oklahoma tallgrass prairie soil, the low relative abundance of Glomeromycota identified here did not arise from the primer set used for PCR amplification, which was also verified by the NCBI primer tool (60). Since arbuscular mycorrhizal fungi form symbioses with many herbaceous land plants, the low relative abundance of Glomeromycota may result from different plant species composition in these ecosystems because fine roots were not removed prior to DNA extraction and rhizosphere soil and bulk soil were not specifically distinguished during sampling process in either study.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, yeasts possess more genes encoding stress tolerance traits than do free‐living filamentous fungi (Treseder & Lennon, ). Others have noted increases in taxonomic groups dominated by free‐living filamentous fungi (Deslippe et al ., ; Xiong et al ., ; Semenova et al ., ) and ectomycorrhizal fungi (Clemmensen et al ., ; Allison & Treseder, ; Deslippe et al ., ; Penton et al ., ) in warming manipulations. Warming may have alleviated cold stress for free‐living filamentous fungi, allowing them to proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fungi are responsible for most of the breakdown of organic C compounds in high latitudes, especially those in more recalcitrant forms (Dighton, ; Ponge, ; van der Heijden et al ., ). Previous field studies have reported shifts in fungal community composition under experimental warming (Clemmensen et al ., ; Allison & Treseder, ; Allison et al ., ; Deslippe et al ., , ; Penton et al ., ; Xiong et al ., ). Fungal responses to increases in soil temperature could have important consequences for global climate.…”
Section: Introductionmentioning
confidence: 99%